Willingness to change car use to commute to the UPTC main campus, Colombia: A hybrid discrete choice modeling approach (2019)
This paper studies the willingness to change car use when commuting to a university campus. We estimated a hybrid discrete choice (HDC) model to test the hypothesis that, in addition to traditional tangible attributes, the willingness to change car use to more sustainable transportation modes also depends on the pro-environmental attitude and the perceived convenience of each transportation alternative. We found that teachers have better pro-environmental attitudes than students and administrative staff, but senior individuals and people who own an above-average priced car have negative effects on this attitude. We concluded that in addition to car ownership, the price of a car is also a decisive factor in the willingness to change car use. On-campus parking fees were identified as a key variable for reducing car use when commuting to campus and for financing more sustainable transportation modes. This paper contributes to the literature on sustainable mobility on university campuses and is the first based on an HDC modeling approach that integrates tangible attributes and latent variables into this context. © 2019 Luis Márquez, Luis F. Macea, & Jose J. Soto.